Best Answer

x(x - 17)(x - 1)

Factorising x3 - 18x2 + 17x:

Common factor x of all terms:

x(x2 - 18x + 17)

17 = -1 x -17, -1 + -17 = -18:

x(x - 1)(x - 17)

Q: X3 - 18x2 plus 17x

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x+1)(x+5)(x+2)

x3 + x2 - 17x + 15 = (x - 1)(x - 3)(x + 5). Thus, the zeros are 1, 3, and -5. All three zeros are rational.

18x2 + 15x + 2 = (3x + 2)(6x + 1)

(x + 3)3 (x + 3) (x + 3) (x + 3) (x2 + 6x + 9) (x + 3) x3 + 6x2 + 9x + 3x2 + 18x + 27 x3 + 18x2 + 27x + 27

3x2 + 17x + c = 0, rearranging gives c = -3x2 - 17x

Related questions

(x+1)(x+5)(x+2)

x3 + x2 - 17x + 15 = (x - 1)(x - 3)(x + 5). Thus, the zeros are 1, 3, and -5. All three zeros are rational.

(x + 1)(x + 3)(x - 5)

18x2 + 15x + 2 = (3x + 2)(6x + 1)

(x + 3)3 (x + 3) (x + 3) (x + 3) (x2 + 6x + 9) (x + 3) x3 + 6x2 + 9x + 3x2 + 18x + 27 x3 + 18x2 + 27x + 27

3x2 + 17x + c = 0, rearranging gives c = -3x2 - 17x

Dividend: 4x^4 -x^2 +17x^2 +11x +4 Divisor: 4x +3 Quotient: x^3 -x^2 +5x -1 Remainder: 7

108x2-102x+24 Simplified by dividing all terms by 6: 18x2-17x+4 When factorised: (9x-4)(2x-1) With a question like this using the quadratic equation formula will help.

17x-3 = 14

It is 1.17x

17x + 9

17x + 13